THE PLACE OF ARTIFICIAL INTELLIGENCE IN THE LEGAL SYSTEM - Paramonova, Оlexandra; Varava, Iryna (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2023)
The purpose of the article is to analyze the current state of legal regulation of the use of artificial intelligence and the prospects for further improvement of Ukrainian legislation in this area. The methodological basis of the research is general scientific and specifically legal methods of cognition, with the help of which various scientific approaches to determining the place of artificial intelligence in the legal system, developing the principles of human interaction with autonomous robots and artificial intelligence, analyzing the understanding of the concept and clarifying the essence of legal fictions have been analyzed, and as well as their significance in the legal sphere. The main methods used in this scientific research were the method of analysis and synthesis and the contextual search method of cognition, which made it possible to establish and distinguish the qualitative characteristics of the phenomenon under study. Results: a detailed analysis of the current Civil Ukrainian legislation showed that in the Ukrainian legal field we can consider artificial intelligence only as an object of intellectual property law, which is not endowed with the features of a subject. This approach is, to some extent, outdated and requires reform of the legislation related to the regulation of artificial intelligence. This process should be systematic and structured. A study of the literature shows that to date, the legal status of artificial intelligence cannot be derived from the model of a natural person. Because then artificial intelligence will have human rights - the right to dignity, inviolability, reward, citizenship, etc. This contradicts the Charter of Fundamental Rights of the EU and the Convention on the Protection of Human Rights and Fundamental Freedoms. Nor can legal status be derived from the model of a legal entity, as it presupposes the presence of people who represent and manage it. Accordingly, artificial intelligence can be introduced into the legal system as a new participant in legal relations, the nature of which combines individual features of a physical and legal entity, taking into account the relevant specifics. The article pays attention to the Concept of updating the Civil Code of Ukraine, which sets the task of determining the principles of human interaction with autonomous robots and artificial intelligence in the process of normative design. Discussion: in order to approach the issue of legal personality of artificial intelligence, it is necessary to recognize at the level of philosophical perception by society that artificial intelligence will not be a product, invention, program, useful model, etc., and the developer (or group of developers) of artificial intelligence will not own it proprietary copyrights, and only non-property ones will belong. Accordingly, artificial intelligence should receive certain rights and obligations, established by the relevant legislative acts. The further perspectives of the research are defined as the analysis of the problems of property rights and copyright in relation to works produced with the help of artificial intelligence.